FORMULASI DAN EVALUASI SEDIAAN TABLET HISAP DARI EKSTRAK ETANOL BIJI KOPI ARABIKA (Coffea arabica L.) JAVA PREANGER SEBAGAI ANTIOKSIDAN - Nurul Auliasari; Hisni Uswatun Hasanah; Retty Handayani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Arabica coffee (Coffea arabica L.) Java Preanger is the best coffee from West Java which is better known internationally as Java Preanger. One of the secondary metabolites found in Arabica coffee beans and efficacious as an antioxidant is chlorogenic acid. Lozenges were made by wet granulation method with various concentrations of coffee extract 5%, 10% and 15%. The resulting preparation was then evaluated for its physical and antioxidant activity. Physical evaluation includes organoleptic tests, weight uniformity, size uniformity, hardness, friability, frictionibility and disintegration time. Meanwhile, the antioxidant activity test was carried out using the ABTS method. Based on the results of the physical evaluation, the formulation that meets the requirements is formula 3 (F3) with a coffee bean extract concentration of 15% and has the highest antioxidant activity with an IC50 value of 27.915 ppm.